DOWNTONERS IN JOURNALISTIC ARTICLES - Djatmika Djatmika (Universitas Muhammadiyah Surakarta, 2009)
The paper discusses the exploitation of euphemistic expressions in printed mediato soften words or phrases considered to be vulgar or profane or negative. Severaltexts from The Jakarta Post were taken as the data source and all expressions in suchtexts downtoning the other negative ones were taken as the data for the analysis.The results show that the softening expressions in the forms of euphemistic expressions are created through two types of process, namely semantic shift and metaphorical transfer. Meanwhile, the motive behind the usage of the expressions is only one, i.e. because of the fear of causing psychic pain to the other participant(s). Having seen the types of and the motive behind of the euphemistic expressions exploited in journalistic articles, the writer as well as the readers of such texts can expectedly understand the message accommodated by the texts easily.Keywords: downtoner, euphemism, expressions, journalism, texts.